UTILIZING MIND MAPPING MODEL TO IMPROVE STUDENTS’ LEARNING OUTCOMES AT GRADE 4 SD N 02 MEGAWON KUDUS - Mayalinda Siska Harwanti; Ika Ari Pratiwi; Deka Setiawan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This classroom action research was carried out at grade IV SD N 02 Megawon involving 25 students. The research was conducted in two cycles; each cycle consisted of four stages, namely planning, implementation, observation, and reflection. The independent variable in this study was the Mind Mapping model, while the dependent variable was learning outcomes. The data were analyzed quantitatively and qualitatively. The results showed that the Mind Mapping model improved students’ learning outcomes on theme 5. It was found that the percentage of learning outcomes in cycle I was 40% and increased to 60% in cycle II. Then, the percentage of students’ activity in cycle I was 80% (good criteria) and increased to 95% in cycle II. This improvement was supported by the teacher’s skills in managing learning, which reached 76.78% in cycle I and increased to 83.9% in cycle II. Thus, the Mind Mapping model improved students’ learning outcomes on theme 5 at grade IV SD N 02 Megawon.